A case study of the association between adolescent idiopathic scoliosis, weight training and shoulder dislocation - Marian Constantin (Annals of Musculoskeletal Medicine - Peertechz Publications, 2023)
This study shows a rare association between the anomalous position of the shoulder girdle, due to scoliosis, with altered shoulder kinematics, injury of joint capsule ligaments and rotator cuff tendons, and shoulder dislocation due to a traumatic event. The subject has developed adolescent idiopathic scoliosis, with convex curvatures to the right side in the lower region of the thorax (with the Cobb angle of 13 degrees) and to the left side of the upper region of the thorax (with the Cobb angle of 24-degrees), both of them with the axial rotation of vertebra and with visible gibbosities. The upper axial rotation has a 6.5-degree, which causes an unbalance between the two shoulder girdles. In normal situations, the shoulder joint is turned 30 degrees anterior to the coronal plane, but in his case, the right shoulder girdle is pulled 28 degrees anterior by the groove, and the left one is pushed 34.5 degrees anterior by the gibbosity. The major effect of shoulder girdle unbalance appears to be the maximum extension of the upper limbs when the hands can't be aligned to the coronal plane and this is an important risk factor for the injuries of the left shoulder joint, while some weight training exercises are performed.